A model for the growth of mariculture kelp Saccharina japonica in Sanggou Bay, China - J Zhang (Inter-Research, 2016)
The kelp Saccharina japonica is one of the most important mariculture species in China. To predict kelp growth and provide a component for a general multitrophic ecosystem model, a dynamic individual growth model was developed to evaluate environmental effects on kelp growth. This model was calibrated and validated using data from 2 annual mariculture cycles (2008-2009, 2011-2012) from Sanggou Bay, China. Gross growth of S. japonica was described as functions of temperature, light and nutrient contents in plant tissues (internal nutrients), and nitrogen (N) and phosphorus (P) in seawater. Net growth was defined as gross growth minus respiration. The simulation results showed that nutrients were the key limiting factor for growth throughout the kelp growth cycle, whereas both temperature and light only limited kelp growth during simulation days 60-120, i.e. from 1 January to the end of February. Scenario simulations showed that fertilizing with nitrogen could improve kelp growth by as much as 4.4 times. The model also predicted that individual dry weight of S. japonica would increase by 18% when lifting the culture ropes up to the surface. Sensitivity analysis indicates that the empirical coefficient of respiration (r), maximum growth rate (μmax) and minimum internal quota for nitrogen (Nimin) were among the most sensitive parameters. This model shows that the introduction of culture methods such as cage culture, which allows more effective fertilization and depth control, would result in more effective kelp farming.